Living independently: Tribulations of the non-resident students in Jengka / Rahimah Abd. Wahab - Abd. Wahab, Rahimah (2009)
The recent large intake of students in the state campuses has necessitated certain drastic actions to be taken by the campus administrators, Any increase in student intake without the corresponding increase in related infrastructure and facilities will create a lot of problems. One particular effect of this is the increase in the number of non-resident students. While the matter has been dealt with in a careful manner so as to minimise the effects on students, there are still a substantial number of students who have had to live off-campus. This study has discovered that problems relating to finances and transportation are ranked highest among the many problems faced. The high rental rates and scarcity of rentals are also among the sources of grievance for these students. It is recommended that efforts be taken to better look after these students' welfare and prevent them from being taken advantage of by irresponsible house-owners.